EFEKTIVITAS IMPLEMENTASI KEBIJAKAN PAJAK RUMAH KOS (Studi Di Kabupaten Banyumas) - Bendiktus Gulo; Bambang Agus Pramuka; Rasyid Mei Mustafa; Uswatun Hasanah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
The boarding house tax is one of the local tax objects that include in the hotel tax which is one of the sources of local taxes used to contribute to regional income. However, the implementation of the boarding house collection policy is still not effective in Banyumas Regency. so that, the realization of revenue from the boarding house tax is still low and far from the expectations of the Banyumas Regency government. The purpose of this study is to see and analyze the reasons why the implementation of the boarding house tax in Banyumas Regency is not effective. The type of research used is descriptive qualitative research. The informants of this research are Badan Pendapatan Daerah Banyumas (Bapenda) staff, boarding house owners, and local village administrations. Data collection techniques in this research are used semi-structured interviews, observation, and documentation. The data analysis technique in this study uses the Miles and Huberman model whose activities include data reduction, data display, and conclusion. The results of this study indicate that: (1) Socialization of the boarding house tax policy has not been carried out optimally, and there is a lack of coordination between Bapenda and the local village government. (2) The Bapenda staff in carrying out policy implementation is still inadequate and doesn't have special inspection staff, (3) Bapenda is still not serious in maximizing the potential for boarding house taxes. (4) The Self Assessment System as a boarding house tax collection system is an obstacle to the realization of house tax collection because Bapenda does not have more control over collecting boarding house taxes. (5) The awareness of boarding house taxpayers is still very low in Banyumas Regency. (6) boarding house tax regulations are still not detailed and specifically regulate the boarding house tax.